Cobalt and its compounds: update on genotoxic and carcinogenic activities. (9th August 2018) - Lison, D.; van den Brule, S.; Van Maele-Fabry, G.
Abstract: This article summarizes recent experimental and epidemiological data on the genotoxic and carcinogenic activities of cobalt compounds. Emphasis is on the respiratory system, but endogenous exposure from Co-containing alloys used in endoprostheses, and limited data on nanomaterials and oral exposures are also considered. Two groups of cobalt compounds are differentiated on the basis of their mechanisms of toxicity: (1) those essentially involving the solubilization of Co(II) ions, and (2) metallic materials for which both surface corrosion and release of Co(II) ions act in concert. For both groups, identified genotoxic and carcinogenic mechanisms are non-stochastic and thus expected to exhibit a threshold. Cobalt compounds should, therefore, be considered as genotoxic carcinogens with a practical threshold. Accumulating evidence indicates that chronic inhalation of cobalt compounds can induce respiratory tumors locally. No evidence of systemic carcinogenicity upon inhalation, oral or endogenous exposure is available. The scarce data available for Co-based nanosized materials does not allow deriving a specific mode of action or assessment for these species.